THU0145 Low Agreement Between Clinical Practice and Centralized Lecture Using the Sharp/Van DER Heijde Score in Patients with Early RA. Results from the Gladar Multinational Cohort. (9th June 2015) - Massardo, L.; PonsEstel, B.; Pineda, C.; Soriano, E.; Cardiel, M.; Galarza, C.; Levy, R.; Sacnum, M.; Caballero, C.V.; Acevedo, E.; Bianchi, W.; González, H.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by synovial inflammation leading to both cartilage destruction and bone erosions. Early identification of patients with RA, and in particular those with erosive course of the disease would allow a timely therapeutic strategy for cartilage and bone protection. Objectives: To investigate the degree of agreement between local expert rheumatologists and central trained readers in the detection of erosions (presence/absence) on plain radiographs of hands and feet. Methods: Patients with early RA (<1 year symptoms) were included in the multinational Latin American RA (GLADAR) cohort (46 participating centers in 14 Latin American countries). A set of baseline hands and feet radiographs were read by two trained readers (radiologist and rheumatologists) in a radiology center in Mexico City, who centrally scored baseline radiographs according to the Sharp/van der Heijde score, erosion 0-280 scale. The same set of radiographs have been rated as erosive/non erosive locally and the fulfilment of radiographic changes criteria for the classification of RA 1987 at baseline had been registered. Agreements and misclassification were calculated (kappa values). Results: From 1069 patients in the GLADAR cohort, there were 516 RA patients with hands and feet radiographs available for standardized radiographic scoring system. According to local and central reading 137 patients (26.6%) and 276 patients (53.5%) displayed erosions, respectively. Agreement between local and central reading was poor (kappa =0.171). From a total of 525 patients with hands radiographs available for standardized scoring, according to local reading 153 (29.1%) fulfilled the radiographic changes criteria RA 1987, whereas central reading showed that 227 (43.2%) presented hand erosions. Again, agreement was poor (kappa =0.120). Conclusions: In patients with early RA trained readers and local rheumatologists agreed poorly on the recognition of erosions. This is relevant as therapeutic decisions may change in the presence of erosions and indicate the necessity of more/better training for radiologists/rheumatologists in evaluating articular damage in RA in LA. References: Early Rheumatoid Arthritis in Latin America: Low Socioeconomic Status Related to High Disease Activity at Baseline. Arthritis Care & Research 2012; 64: 1135-1143 Treatment of Early Rheumatoid Arthritis in a Multinational Inception Cohort of Latin American Patients. The GLADAR Experience. J Clin Rheumatol 2012; 18: 327-335 Acknowledgements: To Dr. Daniel E. Furst, Geffen School of Medicine, University of California Los Angeles Disclosure of Interest: L. Massardo Grant/research support from: Abbott, B. PonsEstel Grant/research support from: Abbott, C. Pineda Grant/research support from: Abbott, E. Soriano Grant/research support from: Abbott, M. Cardiel Grant/research support from: Abbott, C. Galarza Grant/research support from: Abbott, R. Levy Grant/research support from: Abbott, M. Sacnum Grant/research support from: Abbott, C. V. Caballero Grant/research support from: Abbott, E. Acevedo Grant/research support from: Abbott, W. Bianchi Grant/research support from: Abbott, H. González Grant/research support from: Abbott, R. Montúfar Grant/research support from: Abbott, R. Pinto Grant/research support from: Abbott, L. A. Ramírez Grant/research support from: Abbott, C. Zerbini Grant/research support from: Abbott